Grand strategies in war and peace - Kennedy, Paul M. 1945- (Yale University Press, 1991)
Examines how the US, the Soviet Union and various European powers have developed their grand Strategies - how they have integrated their political, economic and military goals in order to preserve their long-term interests in times of war and peace.